STRATEGI PENGUATAN NASIONALISME SISWA MELALUI EKSTRAKURIKULER PRAMUKA DAN PASKIBRA: KAJIAN KOMPARATIF - Hur’aini; Edy Herianto; Bagdawansyah Alqadri; Basariah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to comparatively examine the role of Scout and Flag-Raising Troop (Paskibra) extracurricular activities in strengthening students’ nationalism. The research employed a quantitative approach using a causal-comparative design. Data were collected through questionnaires and documentation involving students who were both active and inactive in Scout and Paskibra activities. The sample consisted of 98 students selected proportionally based on their participation. Data analysis was conducted using the Mann-Whitney U test due to the non-normal distribution. The results revealed that participation in Paskibra had a significant positive impact on students’ nationalism, whereas participation in Scout activities showed no significant effect. However, students actively involved in Paskibra had relatively higher nationalism scores compared to other groups. These findings emphasize that the effectiveness of extracurricular activities in fostering nationalist character is highly influenced by the quality of student engagement and the nature of the program. Therefore, structured, consistent, and value-oriented extracurricular programs such as Paskibra can serve as an effective strategy to strengthen students' nationalism in schools.